Common substance use disorders in older adults. Issue 1 (31st March 2020) - Seim, Lynsey; Vijapura, Priyanka; Pagali, Sandeep; Burton, M Caroline
ABSTRACT: Substance use disorder prevalence in older adults is increasing as the baby boom generation ages. Of the different substances with concern for misuse and use disorder, alcohol, prescription drugs, and illicit drugs are the leading causes. High-risk drinking and alcohol use disorder is the leading substance use disorder in older adults. Prescription drug misuse and use disorder in older adults are the second leading cause for substance use disorder and most commonly involves prescription opioids and benzodiazepines. Illicit drug use in older adults is also increasing. Substance use disorders are difficult to recognize in older adults due to medical comorbidity, neurocognitive impairment, and functional decline. Older adults are also more susceptible to drug effects due to decreased hepatic and renal clearance of the substances. Older adults should be screened and assessed for substance use disorders, and when diagnosed, non-pharmacologic as well as pharmacologic intervention should be performed.